Modern Methods of Assessing the Condition of the Mother and Fetus during Pregnancy - Usmonova Zarina Muxtor qizi (American Journal of Bioscience and Clinical Integrity, 2024)
Your doctor may recommend a variety of screenings, tests, and imaging techniques during pregnancy. These tests are designed to provide information about your baby’s health and help optimize your child’s prenatal care and development. Genetic testing helps identify the potential for certain genetic disorders before birth. First trimester screening is a combination of fetal ultrasound and maternal blood testing. This screening process helps determine the risk of the fetus having certain birth defects. Second-trimester prenatal screening may include several blood tests called multiple markers. These signs provide information about the risk of having a baby with certain genetic diseases or birth defects. You can have an ultrasound at different times of your pregnancy to check the growth of the fetus, estimate the due date and look for any structural abnormalities in the baby. Additional testing during pregnancy may include amniocentesis, chorionic villus sampling (CVS), fetal monitoring, glucose testing, and group B streptococcal. Genetic screening Many genetic abnormalities can be detected before birth. Your doctor or midwife may recommend genetic testing during pregnancy if you or your partner have a family history of genetic disorders. If you have a fetus or baby with a genetic abnormality, you may have genetic testing.